Applying Gamification in Teaching English as a Foreign Language in Algerian Primary School The Case Study of Teachers of English in Primary Schools, Souk-Ahras - Dounia TORCHE (My University, 2024)
Abstract This study aims at highlighting the importance of applying gamification to teach English in Algerian primary school as well as exploring how gamification can develop primary school students’ English language. Gamification, or the use of game design features to engage learners or improve academic achievement, has emerged as a potential method for foreign language learning. This descriptive and exploratory research employed a quantitative data collection method. To achieve the goals of our research, this study relied on one instrument for data collection: an online questionnaire administered to 21n English language teachers in primary schools in Souk-Ahras, Algeria who were selected conveniently. The data collected was analyzed quantitatively employing both descriptive statistics to summarize the data's main features and inferential statistics to draw conclusions and make predictions. The results revealed that teachers face many obstacles while teaching English such as lack of teaching materials, poor classroom management, and overcrowded classes. The findings of this study indicated that applying gamification could be efficient in learning English as a foreign language in Algerian primary schools as it boosts students’ motivation to learn English ---------------------- ملخص تهدف هذه الدراسة إلى تسليط الضوء على أهمية تطبيق الألعاب لتدريس اللغة الإنجليزية في المدرسة الابتدائية الجزائرية بالإضافة إلى استكشاف كيفية تطوير اللغة الإنجليزية لطلاب المدارس الابتدائية. ظهرت الألعاب، أو استخدام ميزات تصميم الألعاب لإشراك المتعلمين أو تحسين التحصيل الأكاديمي، كطريقة محتملة لتعلم اللغة الأجنبية. استخدم هذا البحث الوصفي والاستكشافي طريقة جمع البيانات الكمية. لتحقيق أهداف بحثنا، اعتمدت هذه الدراسة على أداة واحدة لجمع البيانات: استبيان عبر الإنترنت يتم إدارته لمعلمي اللغة الإنجليزية في المدارس الابتدائية في سوق أهراس، الجزائر. تم تحليل البيانات التي تم جمعها كميًا. كشفت النتائج أن المعلمين يواجهون العديد من العقبات أثناء تدريس اللغة الإنجليزية مثل نقص الأدوات التعليمية وسوء إدارة الفصول الدراسية واكتظاظ الفصول الدراسية. أشارت نتائج هذه الدراسة إلى أن تطبيق الألعاب يمكن أن يكون فعالاً في تعلم اللغة الإنجليزية كلغة أجنبية في المدارس الابتدائية الجزائرية لأنه يعزز دافع الطلاب لتعلم اللغة الإنجليزية ------------------- Résumé Cette étude vise à souligner l’importance de l’application de la gamification pour enseigner l’anglais à l’école primaire algérienne ainsi qu’à explorer comment la gamification peut développer la langue anglaise des élèves du primaire. La ludification, ou l’utilisation de fonctionnalités de conception de jeux pour engager les apprenants ou améliorer les résultats scolaires, est devenue une méthode potentielle pour l’apprentissage des langues étrangères. Cette recherche descriptive et exploratoire a utilisé une méthode de collecte de données quantitatives. Pour atteindre les objectifs de notre recherche, cette étude s’est appuyée sur un instrument de collecte de données : un questionnaire en ligne administré aux enseignants de langue anglaise dans les écoles primaires de Souk-Ahras, en Algérie. Les données recueillies ont été analysées quantitativement. Les résultats ont révélé que les enseignants font face à de nombreux obstacles lors de l’enseignement de l’anglais, tels que le manque de matériel pédagogique, une mauvaise gestion de la salle de classe et des classes surpeuplées. Les résultats de cette étude ont indiqué que l’application de la ludification pourrait être efficace dans l’apprentissage de l’anglais comme langue étrangère dans les écoles primaires algériennes, car elle stimule la motivation des élèves à apprendre l’anglais.